EVALUATION OF SOME ANTIBIOTICS’RESISTANCE OF DIFFERENT ORAL BACTERIA TYPES ISOLATED FROM PATIENTS WITH GINGIVITIS AND PERIODONTITIS - MUDHAFAR ABDEL-RAHMAN, ABEER; FANAR SALEH, NABRA (University of Thi-Qar Journal of Science, 2017)
Background Periodontal diseases are highly prevalent in Iraq. They may become serious conditions if they faced by unsuitable treatment and resulting in particularly cardiovascular systemic disorders. Further, antibiotic resistance in general has been witnessed prevalence, which may lead to failure of periodontal disease treatment. The aim of this study is evaluation of susceptibility and resistance to different antibiotics by dental plaque bacterial isolates.Material and methods Thirty seven infected patients were included in this study. From their dental plaque, samples were taken aseptically then bacteria has been isolated as well as antibiotic susceptibility tests agar diffusion methods had been applied. Results Among three types of bacteria, Streptococcus mutans occupied the largest percentage (62%) in dental plaque isolates. Imipenem registered profound susceptibility (78.3%) via Streptococcus mutans followed by each of erythromycin, ciprofloxacin, and ceftriaxone (60.9%). This pathogen isolates showed resistance to amikacin, chloramphenicol, tetracycline and amoxicillin. Pseudomonas aeruginosa appeared the highest susceptibility to chloramphenicol and ceftriaxone by (90%) while Staphylococcus aureus had been existed complete susceptibility to imipenem (100%) followed directly by tetracycline and chloramphenicol by about (75%) of each. The lowest susceptibility was resulted toward amoxicillin, amikacin, and ciprofloxacin with (25%). Generally speaking, amoxicillin exposed to highest resistance (70.3%) in comparison to others, whereas both of imipenem and ceftriaxone witnessed highest susceptibility (67.6%) by the same pathogens. Conclusions Amoxicillin occupied the first position in bacterial resistance, this may support the assumption that improper administration of amoxicillin will lead to therapy failure. KEYWORDS: Antibiotics, Gingivitis, Periodontitis, Resistance, Susceptibility.